2006
DOI: 10.1515/jpm.2006.092
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of fetal behavior of growth restricted fetuses by 4D sonography

Abstract: Recent data on IUGR fetuses obtained by 4D sonography are stimulating and might result in a more effective strategy to assess development before birth. The results of this study may encourage future use of 4D ultrasound for quantitative and qualitative assessment of fetal behavior as possible indicators of the neurological condition in IUGR fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 31 publications
1
66
0
1
Order By: Relevance
“…A study investigating the multifactorial etiology of CP found a strong association between FGR and CP: FGR was found in 34 % in a series of 213 children diagnosed with CP [37] . Recent advances in understanding CP and other neurodevelopmental disorders as a result of insults during the prenatal period are about to induce a paradigm shift in jurisdiction in unfavorable perinatal outcome [1] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study investigating the multifactorial etiology of CP found a strong association between FGR and CP: FGR was found in 34 % in a series of 213 children diagnosed with CP [37] . Recent advances in understanding CP and other neurodevelopmental disorders as a result of insults during the prenatal period are about to induce a paradigm shift in jurisdiction in unfavorable perinatal outcome [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, it is not surprising that adverse pregnancy conditions, such as gestosis, FGR, famine during pregnancy (protein-energy malnutrition), and severe chronic maternal stress or depression have been linked to altered fetal movement patterns, echogenicity changes of the fetal brain, to higher incidence of neurodevelopmental disorders in childhood, and to occurrence of autism, schizophrenia, and epilepsy in the adult [1,3,5,9,12,16,32,40,41] .…”
Section: Fetal Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…[33][34][35]37,[39][40][41] All studies focused on the assessment of fetal facial expressions and movements, and fetal hand to face movements (Figs 6A to 8), because the viewing area was limited to that of the transabdominal probe. Kurjak et al 37 were the first to use 4D sonography to study 10 healthy fetuses for 15 minutes at 30 to 33 weeks.…”
Section: Late Second and Third Trimestersmentioning
confidence: 99%